Traditional Classification, Perception, and Preferences for Tallow Tree (Pentadesma butyracea Sabine) Organs in Benin: Implications for domestication and conservation - Houédjissin, Serge S.; Azokpota, Paulin; Assogbadjo, Achille; Ahanhanzo, Corneille; Hounhouigan, Joseph D. (Ethnobotany Research and Applications, 2016)
The present study examined farmer’s indigenous knowledge on morphological variation, preference in product traits, management practices, and regeneration of Pentadesma butyracea Sabine. Surveys were conducted on a total of 131 users of different ages randomly selected from seven different sociocultural groups (Anii, Kotocoli, Nagot, Boo, Ditamari, Natimba and Waama) taking into account gender differences in Benin. Principal component analysis was carried out to identify correlations between the characteristics of P. butyracea. Local people in the twelve villages investigated used 13 criteria (height, trunk diameter, trunk color, trunk structure, distance from water, tree age, fruit pulp color, fruit size, fruit shape, number of seeds per fruit, seed color, seed size, and seed shape) to differentiate P. butyracea trees growing in traditional agroforestry systems. Older people were found to have greater knowledge than younger people to distinguish P. butyracea. Importantly, 77% of respondents of all ethnic groups confirmed that no protection measure was taken to conserve P. butyracea trees. This identified knowledge can constitute a guarantee for the development of strategies for conservation, domestication, and sustainable use of P. butyracea genetic resources because one of the best ways to validate our results to local people is to consider their knowledge and to promote the development of their experiences. Résumé La présente étude a mis en évidence les connaissances endogènes des populations locales sur la variation morphologique, leurs préférences (traits désirables et non désirables), les procédures de gestion locale et la régénération de Pentadesma butyracea Sabine au Bénin. Au total, 131 personnes, de différents âges et sexes, appartenant à sept groupes ethniques différents (Anii, Kotocoli, Nagot, Boo, Ditamari, Natimba et Waama) ont été aléatoirement interviewées. L’analyse en composante principale (ACP) a été effectuée pour expliquer la corrélation entre les caractéristiques de P. butyracea. Dans les douze localités enquêtées, les populations utilisent 13 critères (taille, dimension du tronc, couleur du tronc, structure du tronc, distance de l’arbre de l’eau, âge de l’arbre, dimension du fruit, nombre de graines par fruit) pour différencier les arbres de P. butyracea. Cependant, l’arbre de P. butyracea est plus connu par les personnes âgées. Cette étude a également prouvé que 77.2% des interviewés, toutes ethnies confondues, ont confirmé qu’aucune mesure de protection n’a été prise pour conserver les arbres de P. butyracea. Les savoirs paysans recensés ici, peuvent constituer un gage pour le développement de stratégies de conservation, de domestication et d’utilisation durable des ressources génétiques de P. butyracea, car l’une des voies pour mieux valider nos résultats auprès des populations rurales est de tenir compte de leurs savoirs, et cela favorise la valorisation de leurs expériences.